Solution‐Processed Pure Sulfide Cu2(Zn0.6Cd0.4)SnS4 Solar Cells with Efficiency 10.8% Using Ultrathin CuO Intermediate Layer. Issue 9 (4th September 2020) - Zhuk, Siarhei; Wong, Terence Kin Shun; Petrović, Miloš; Kymakis, Emmanuel; Hadke, Shreyash Sudhakar; Lie, Stener; Wong, Lydia Helena; Sonar, Prashant; Dey, Avishek; Krishnamurthy, Satheesh; Dalapati, Goutam Kumar
Abstract : Interface Engineering In article number 2000293, Kin Shun Wong, Goutam Kumar Dalapati, and co‐workers develop stable and efficient Cu2 (Zn0.6 Cd0.4 )SnS4 (CZCTS) thin film solar cells using a low cost solution‐based method and ultra‐thin cupric oxide (CuO) interface engineering. Power conversion efficiency of 10.77% is achieved for the CZCTS devices with 4 nm cupric oxide interface layer. Incorporating ultra‐thin CuO enhances performance and stability of the device and opens up the opportunity for large scale photovoltaic deployment using earth abundant materials.